Application of the disposable eyewash container with modified drainage pack in the irrigation of the conjunctival sac (引流袋改良的一次性受水器在结膜囊冲洗中的应用) - XIE Lingzhi (谢玲芝); CHE Lina (车丽娜); YU Jijiao (虞吉娇) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of applying a disposable eyewash container with modified drainage pack in the irrigation of the conjunctival sac. Methods Totally 140 patients undergoing ophthalmologic operation were randomly divided into the observation group and the control group, with 70 cases in each group. Irrigation of the conjunctival sac was performed with a normal eyewash container in the control group, while a disposable eyewash container with modified drainage pack was adopted in the irrigation of the conjunctival sac in the observation group. The effect of irrigation and related nursing was evaluated. Results Application of eyewash container with modified drainage pack was associated with higher comfort degree, longer irrigation time, lower incidence of leakage and higher satisfaction degree (P＜0. 01). Conclusion Application of disposable eyewash container with modified drainage pack could overcome many shortcomings of using eyewash container, including leakage of irrigation fluid and poor patient compliance. (目的 探讨引流袋改良的一次性受水器在结膜囊冲洗中的应用效果。方法 140例眼科手术患者分为观察组和对照组, 各70例。对照组采用常规受水器进行术前结膜囊冲洗, 观察组引流袋改良的一次性受水器冲洗结膜囊。观察2组的护理效果。结果 与对照组使用常规受水器相比, 研究组使用引流袋改良的一次性受水器后患者舒适度评价提高, 冲洗时间延长, 受水器漏水发生率降低, 对受水器使用的满意度提高, 差异有统计学意义(P＜0. 01)。结论 引流袋改良的一次性受水器克服传统受水器的多项弊端, 解决冲洗时冲洗液外溢和患者配合困难的问题, 有效提高患者的舒适度和满意度。)